New interview and observation measures of the broader autism phenotype: Impressions of interviewee measure - Pickles, A.; Parr, J.; Rutter, M.; De Jonge, M.; Wallace, S.; Le Couteur, A.; Van Engeland, H.; Wittemeyer, K.; McConachie, H.; Roge, B.; Mantoulan, C.; Pedersen, L.; et al. (Springer New York LLC, 2013)
A 20 item observational measure of social functioning, the Impression of Interviewee rating scale, is one of three measures devised to assess the broader autism phenotype. The sample studied included families containing at least two individuals with autism spectrum disorder; observations were undertaken by the researcher who interviewed the subject. An exploratory factor analysis suggested a single factor was most appropriate (Cronbach's a of 0.78). There was a modest but significant retest correlation of 0.42. Correlations between live ratings and blind consensus ratings of vignettes were high (0.93). Correlations with the interview measures were moderate but statistically significant. In conclusion, the observational scale provides a promising start but further work is required before general use can be recommended. © 2013 Springer Science+Business Media New York.